STUDI DESKRIPTIF MEMBACA PERMULAAN DI KELAS I-B SDN PANCORAN 07 PAGI TAHUN AJARAN 2019/2020 - Lola Sarah Aulia; Robiatul Munajah (Universitas Trilogi, 2021)
This study aims to describe the inhibiting and supporting factors of prefix reading, as well as to describe the teacher's efforts in overcoming pre-reading problems in class I-B SDN Pancoran 07 Pagi. This research uses a qualitative approach with descriptive methods. Data collection techniques in this study were interviews and observation. The results of this study indicate that there are several inhibiting factors such as: (1) lack of self-confidence, (2) low learning concentration, (3) lack of teacher assertiveness, (4) lack of parental attention. The supporting factors for reading the beginning are: (1) supporting facilities and infrastructure, (2) the existence of a reading corner, (3) peers. While the teacher's efforts that have been made are: (1) The teacher provides additional hours, (2) The learning process is fun.